Stop-event-related potentials from intracranial electrodes reveal a key role of premotor and motor cortices in stopping ongoing movements - Mattia, Maurizio; Spadacenta, Silvia; Pavone, Luigi; Quarato, Pierpaolo; Esposito, Vincenzo; Sparano, Antonio; Sebastiano, Fabio; Di Gennaro, Giancarlo; Morace, Roberta; Cantore, Gianpaolo; Mirabella, Giovanni (Frontiers in Neuroengineering, 2012)
In humans, the ability to withhold manual motor responses seems to rely on a right-lateralized frontal–basal ganglia–thalamic network, including the pre-supplementary motor area and the inferior frontal gyrus (IFG). These areas should drive subthalamic nuclei to implement movement inhibition via the hyperdirect pathway. The output of this network is expected to influence those cortical areas underlying limb movement preparation and initiation, i.e., premotor (PMA) and primary motor (M1) cortices. Electroencephalographic (EEG) studies have shown an enhancement of the N200/P300 complex in the event-related potentials (ERPs) when a planned reaching movement is successfully stopped after the presentation of an infrequent stop-signal. PMA and M1 have been suggested as possible neural sources of this ERP complex but, due to the limited spatial resolution of scalp EEG, it is not yet clear which cortical areas contribute to its generation. To elucidate the role of motor cortices, we recorded epicortical ERPs from the lateral surface of the fronto-temporal lobes of five pharmacoresistant epileptic patients performing a reaching version of the countermanding task while undergoing presurgical monitoring. We consistently found a stereotyped ERP complex on a single-trial level when a movement was successfully cancelled. These ERPs were selectively expressed in M1, PMA, and Brodmann's area (BA) 9 and their onsets preceded the end of the stop process, suggesting a causal involvement in this executive function. Such ERPs also occurred in unsuccessful-stop (US) trials, that is, when subjects moved despite the occurrence of a stop-signal, mostly when they had long reaction times (RTs). These findings support the hypothesis that motor cortices are the final target of the inhibitory command elaborated by the frontal–basal ganglia–thalamic network.